Conservação preventiva da escultura colonial mineira em cedro: um estudo preliminar para estimar flutuações permissíveis de umidade relativa - Alessandra Rosado (2004)
This paper looks to contribute to an estimate of the relative permissible humidity levels for colonial sculptures from the state of Minas Gerais, Brazil. Experiments were carried out to determine humidity levels and the elasticity of cedar when subjected to variations in relative humidity. An interdisciplinary approach was adopted by which, beyond the experiments themselves, historical aspects of eighteenth century sculpture techniques were studied and typologies of degradation related to the hygroscopic behavior of wood were characterized through a comparative analysis of 71 polychromatic cedar sculptures. The cedar wood (cedrela sp) used in the experiments came from the city of São João Evangelista, Minas Gerais and was approximately 21 years old. All of the methodology used in the experiments followed the technical norms prescribed by the Brazilian Association of Technical Norms (ABNT) NBR 7190/97. This project can be considered a work of baseline reference. The results obtained in the experiments, established for the preventive preservation of wood objects, permitted the study of the possibility of using the fluctuations in relative humidity (from 45% to 65%) for the preservation of cedar sculptures from the state of Minas Gerais.